(untitled) (Research, Society and Development, 2020)
Synthetic dyes are used on a large scale in the textile industry and generally their effluents are discharged into rivers, without proper treatment, this fact harms the environment. On the other hand, there are natural dyes which have chemical structures and properties similar to those of synthetic dyes and can be found in fruits, vegetables and flowers. This research is aimed at evaluating the possibility of extracting a natural dye from cashew bagasse, using the magnetic stirring method to favor extraction through molecular interactions between the different solvents evaluated and the pigments present in the cashew stalk. The method used in this work does not require the use of toxic products to obtain the dye, in addition to reusing cashew bagasse, which has little or no purpose after juice extraction. Natural dyes are less harmful to the environment, in agreement with the principles of Green Chemistry, whose ideology is sustainable development in chemical processes and the reduction and reuse of waste. The methodology developed for extracting the natural dye from cashew bagasse proved to be efficient, where the best result obtained was for the extract with sodium hydroxide (NaOH) such as an extracting solvent.